Aerosolized Coal Fly Ash Particles, the Main Cause of Stratospheric Ozone Depletion, not Chlorofluorocarbon Gases - Herndon, J. Marvin; Whiteside, Mark (European Journal of Applied Sciences, 2022)
We present compelling evidence that supports our contention that aerosolized coal fly ash particles are the main agents responsible for stratospheric ozone depletion, not chlorofluorocarbon gases. Aerosolized coal fly ash particles, uplifted to the stratosphere, not only serve as ice-nucleating agents, but are trapped and concentrated in stratospheric clouds, including Polar Stratospheric Clouds. In springtime, as stratospheric clouds begin to melt/evaporate, said ozone-consuming coal fly ash particles are released making them available to react with and consume stratospheric ozone. Ceasing to contaminate the environment with aerosolized coal fly ash will decrease stratospheric ozone destruction, reduce global warming, and will significantly improve human and environmental health.